Frequency-Specific Changes in the Fractional Amplitude of the Low-Frequency Fluctuations in the Default Mode Network in Medication-Free Patients With Bipolar II Depression: A Longitudinal Functional MRI Study - Zhou, Jun; Ma, Xiaoqian; Li, Chunwang; Liao, Aijun; Yang, Zihao; Ren, Honghong; Tang, Jinsong; Li, Jinguang; Li, Zongchang; He, Ying; Chen, Xiaogang (Frontiers in Psychiatry, 2021)
Objective: To examine the treatment-related changes of the fractional amplitude of low-frequency fluctuations (fALFF) in the default mode network (DMN) across different bands after the medication-free patients with bipolar II depression received a 16-week treatment of escitalopram and lithium. Methods: A total of 23 medication-free patients with bipolar II depression and 29 healthy controls (HCs) were recruited. We evaluated the fALFF values of slow 4 (0. 027–0.073 Hz) band and slow 5 (0. 01–0.027 Hz) band of the patients and compared the results with that of the 29 HCs at baseline. After 16-week treatment of escitalopram with lithium, the slow 4 and slow 5 fALFF values of the patients were assessed and compared with the baselines of patients and HCs. The depressive symptoms of bipolar II depression in patients were assessed with a 17-item Hamilton Depression Rating Scale (HDRS) before and after treatment. Results: Treatment-related effects showed increased slow 5 fALFF in cluster D (bilateral medial superior frontal gyrus, bilateral superior frontal gyrus, Right middle frontal gyrus ,and bilateral anterior cingulate), cluster E (bilateral precuneus/posterior cingulate, Left cuneus), and cluster F (left angular, left middle temporal gyrus, left superior temporal gyrus, and left supramarginal gyrus) in comparison with the baseline of the patients. Moreover, a positive association was found between increase in slow 5 fALFF values (follow-up value minus the baseline values) in cluster D and decrease in HDRS scores (baseline HDRS scores minus follow-up HDRS scores) at follow-up, the same association between increase in slow 5 fALFF values and decrease in HDRS scores was found in cluster E . Conclusions: The study reveals the hypoactivity of slow 5 fALFF in the DMN are related to depression symptoms and might be corrected by the administration of escitalopram with lithium, implying that slow 5 fALFF of the DMN plays a key role in bipolar depression.